Liquid Coordination Complexes Formed by the Heterolytic Cleavage of Metal Halides1. Issue 48 (11th October 2013) - Coleman, Fergal; Srinivasan, Geetha; Swadźba‐Kwaśny, Małgorzata
<x xml:space="preserve">Abstract</x> Confused complexes: Reaction of a range of donor molecules with AlCl3 or GaCl3, gives mobile liquids with very high metal contents. They contain statistically distributed mixtures of anionic, cationic, and neutral complexes in equilibrium. These liquid coordination complexes (LCCs), have high conductivity, tunable Lewis acidity, and low vapor pressure.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>